ADVANCED FOREIGN EXPERIENCES IN IMPROVING THE LEGAL FRAMEWORK FOR FINANCIAL CONTROL OVER THE USE OF BUDGET FUNDS (American Journal of Business Management, Economics and Banking, 2025)
This paper examines the historical evolution, institutional structures, and global practices of state financial control. It outlines the major stages in the development of financial oversight systems and highlights the diverse models implemented across countries, including courts of accounts, audit tribunals, and supreme audit institutions.